In Situ Stress Effects on Smooth Blasting: Model Test and Analysis. (7th January 2020) - Yang, Renshu; Fang, Shizheng; Yang, Aiyun; Xie, Huanzhen; Yang, Liyun
Abstract : Most of the roadway excavation is completed by the drilling and blasting method. With the increase of buried depth, the existence of ground stress will generate a significant impact on the rock blasting, especially on the smooth blasting. In this study, self-made homogeneous similar materials and digital image correlation methods were used to determine influence of ground stress on the smooth blasting under uniform explosive charge parameters and various in situ stress conditions. The results show that the crack outline after blasting changes from zigzag to straight in shape, and multifractal calculation results of the rupture section between blastholes show that the fracture surface becomes flatter as ground stress increases, which is conducive to roadway formation. The strain and equivalent strain rate obviously decrease as the distance between the blasthole and measuring points increases. The same trend occurs as the confining pressure goes up. Meanwhile, a postexplosion acoustic wave test indicates that confining pressure inhibits damage of the retained rock, which is consistent with strain and equivalent strain rate results. Finally, we discussed the crack propagation mechanism of rock in smooth blasting.